Sustainable Resource Development in the 21st Century Essays in Memory of Peter Berck - Zilberman, David; Perloff, Jeffrey M.; Spindell Berck, Cyndi (Natural Resource Management and Policy, 2023)
This is an open access book. This edited volume discusses topics in environmental economics with a focus on sustainability, conservation, and responsible resource management. Written in memory of Peter Berck, Professor of Agricultural and Resource Economics at the University of California, Berkeley, the chapters expand upon his insights about the connections between human activities and the natural world. The volume includes a selection of research on agriculture, energy, forestry, fisheries, land use, recycling, and conservation - all parts of the broad question of how natural resources can meet human needs while avoiding environmental degradation. Written from a 21st century perspective, with concerns about climate, renewable energy, biodiversity, and sustainable development, this volume will be of interest to researchers and students of agricultural and resource economics.